2010
DOI: 10.1016/j.bandl.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of naming errors during cortical stimulation mapping: Implications for models of language representation

Abstract: This study reports on the characteristics and distribution of naming errors of patients undergoing cortical stimulation mapping (CSM). During the procedure, electrical stimulation is used to induce temporary functional lesions and locate ‘essential’ language areas for preservation. Under stimulation, patients are shown slides of common objects and asked to name them. Cortical stimulation can lead to a variety of naming errors. In the present study, we aggregate errors across patients to examine the neuroanatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
4
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(163 citation statements)
references
References 65 publications
12
145
4
2
Order By: Relevance
“…Yes, they are, regarding the wealth of experience of DCS and its status as the gold standard for the detection of language-eloquent brain regions. 7,9,26,44,45,62,65 Noninvasive mapping techniques for identifying human language function have to compete with results mapped during awake surgery. Having no other modalities, however, we still do not know exactly the role played by these DCS-identified language-positive points.…”
Section: Discussion Rtms Versus Dcs Language Mappingmentioning
confidence: 99%
See 3 more Smart Citations
“…Yes, they are, regarding the wealth of experience of DCS and its status as the gold standard for the detection of language-eloquent brain regions. 7,9,26,44,45,62,65 Noninvasive mapping techniques for identifying human language function have to compete with results mapped during awake surgery. Having no other modalities, however, we still do not know exactly the role played by these DCS-identified language-positive points.…”
Section: Discussion Rtms Versus Dcs Language Mappingmentioning
confidence: 99%
“…13,17,30,66 This has been shown in several studies and for each of the 3 modalities. 9,30,40 However, it has also been shown that fMRI language mapping is more sensitive to anterior than to posterior language-related cortical regions. 3 The more frequently detected occurrence of positive BOLD signals within the anterior language-related regions could be approved by our study and these circumstances have to be considered in case of assessing the accuracy of fMRI language mapping (Fig.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early models described a serial organization of these naming subprocesses; however, a new framework proposed by Hughes Duffau and colleagues argues that the phonological and semantic subprocesses occur in parallel, with dorsal and ventral streams, in a manner similar to that described by the Hickok-Poeppel model (see Duffau et al, 2014 for an excellent review). 34,61 Although the most common effect of cortical stimulation during naming is no response, 18 when less frequent but specific errors are elicited, they can help further differentiate some selective linguistic subprocesses. For example, visual paraphasias have been reproducibly elicited during stimulation of the basal occipitotemporal cortex.…”
Section: Intraoperative Cortical Mappingmentioning
confidence: 99%